2022
DOI: 10.3389/fphys.2022.890520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress on Production Performance, Redox Status, Intestinal Morphology and Barrier-Related Gene Expression, Cecal Microbiome, and Metabolome in Indigenous Broiler Chickens

Abstract: This study was done to evaluate the effects of heat stress (HS) on production performance, redox status, small intestinal barrier-related parameters, cecal microbiota, and metabolome of indigenous broilers. A total of forty female indigenous broilers (56-day-old) were randomly and equally divided into normal treatment group (NT group, 21.3 ± 1.2°C, 24 h/day) and HS group (32.5 ± 1.4°C, 8 h/day) with five replicates of each for 4 weeks feeding trial. The results showed that the body weight gain (BWG) of broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 69 publications
(91 reference statements)
7
21
0
Order By: Relevance
“…Exposure of broiler chicks to an acute temperature of 32°C for 6 h induced metabolic changes that triggered oxidative stress ( Lin et al, 2006 ). A recent study by Liu et al (2022a) further confirmed that chronic HS (32.5 ± 1.4°C for 8 h/d) for 4 wk induced oxidative stress in broilers evidenced by elevated MDA levels and reduced antioxidant enzymes activity in serum, muscles and small intestines. Enzymatic and non-enzymatic antioxidant defence systems can be internally synthesized or externally supplied in response to oxidative stress and increased due to defence mechanisms against heat-induced oxidative stress ( Akbarian et al, 2016 ; Surai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 70%
“…Exposure of broiler chicks to an acute temperature of 32°C for 6 h induced metabolic changes that triggered oxidative stress ( Lin et al, 2006 ). A recent study by Liu et al (2022a) further confirmed that chronic HS (32.5 ± 1.4°C for 8 h/d) for 4 wk induced oxidative stress in broilers evidenced by elevated MDA levels and reduced antioxidant enzymes activity in serum, muscles and small intestines. Enzymatic and non-enzymatic antioxidant defence systems can be internally synthesized or externally supplied in response to oxidative stress and increased due to defence mechanisms against heat-induced oxidative stress ( Akbarian et al, 2016 ; Surai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 70%
“…Enteral inflammation has been shown to shorten the lifespan of enterocytes and cause crypt hyperplasia and villus atrophy (Smith et al, 2014). These alterations in intestinal epithelium morphology (microarchitecture), along with increased cell apoptosis and reduced cell proliferation, have recently been observed in broiler chickens exposed to HS (He et al, 2018a(He et al, , 2018bLiu et al, 2020Liu et al, , 2022Nanto-Hara et al, 2020). In their pair-feeding study with broilers, Nanto-Hara et al ( 2020) evidenced that intestinal morphological damage and increased intestinal permeability are direct consequences of HS rather than of feed intake reduction induced by HS itself.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…For instance, data from several studies indicate that high ambient temperatures can dramatically shape the GI microbiota. Specifically, it has been demonstrated that HS perturbs the GI microbiota in rats ( Suzuki et al, 1983 , 1989 ), poultry ( Suzuki et al, 1983 , 1989 ; Lan et al, 2004 ; Burkholder et al, 2008 ; Song et al, 2014 ; Wang X. J. et al, 2018 ; He et al, 2019b ; Shi et al, 2019 ; Xing et al, 2019 ; Zhu et al, 2019 ; Liu et al, 2020 ; Wang et al, 2020 ; He et al, 2021 ; Liu et al, 2022 ), dairy cattle ( Chen et al, 2018 ), and pigs ( He et al, 2019a ; Le Sciellour et al, 2019 ; Xiong et al, 2020 ), pushing it to dysbiosis. Dysbiosis (dysbacteriosis) is an alteration in the gut microbiota with an overgrowth of harmful microorganisms, or a depletion of beneficial bacteria, which can weaken the fragile equilibrium between the host and its GI microbiota ( Walker, 2017 ; Ducatelle et al, 2018 ).…”
Section: Heat Stress Effects On Gut Health Of Chickensmentioning
confidence: 99%
See 2 more Smart Citations